2020
DOI: 10.3390/foods10010017
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antioxidant and Antihypertensive Properties during Growth of Lactobacillus helveticus, Lactobacillus rhamnosus and Lactobacillus reuteri on Cow’s Milk: Fermentation and Peptidomics Study

Abstract: Bioactive peptides derived from milk proteins are an active research area. Exhibiting numerous positive physiological effects on digestive, cardiovascular, immune and nervous systems, these peptides thought to be one of the most promising ingredients for functional food. Generally, these peptides are inactive within the parent proteins and can be liberated during milk fermentation by the specific proteolytic systems of various Lactobacillus spp. Here we present the study of milk fermentation by Lactobacillus h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…All three L. helveticus strains were able to cleave over 70% of the β-casein (84% in ATCC15009, 75% in DQHXN-Q32M42, and 73% in DYNDL36-6). These findings are in agreement with the results of Begunova et al [ 26 ]. Notably, β-casein seemed to be more accessible to cleavage and subsequently more hydrolyzed than the αS1-casein, probably because this molecule is considered to be an intrinsically unstructured protein [ 27 ].…”
Section: Resultssupporting
confidence: 94%
“…All three L. helveticus strains were able to cleave over 70% of the β-casein (84% in ATCC15009, 75% in DQHXN-Q32M42, and 73% in DYNDL36-6). These findings are in agreement with the results of Begunova et al [ 26 ]. Notably, β-casein seemed to be more accessible to cleavage and subsequently more hydrolyzed than the αS1-casein, probably because this molecule is considered to be an intrinsically unstructured protein [ 27 ].…”
Section: Resultssupporting
confidence: 94%
“…Various studies have reported the release of this type of compound during fermentation of milk with different lactic acid bacteria, including antihypertensive peptides released by L. rhamnosus GG [12][13][14][15]. Begunova et al [16] determined that the antihypertensive activity of the peptides released by a milk fermentation with a specie of L. rhamnosus, is greater than that compared to other types of lactobacilli, which release a higher concentration of antioxidant peptides. Likewise, it has been observed that the greater antihypertensive capacity is related with long fermentation time.…”
Section: Introductionmentioning
confidence: 99%
“…In relation, it has been shown that an inoculum concentration of 1 × 10 6 CFU/mL is enough to generate free amino groups concentrations close to 1 mg/L of fermented milk inoculated with L. rhamnosus [17,19,43]. Furthermore, other reports found that the higher production of free amino groups in the fermentation with L. casei is related to the higher inulin concentration assay (0.5% of inulin) [44].…”
Section: Discussionmentioning
confidence: 99%